Fabrication of amphiphilic quantum dots towards high-colour-quality light-emitting devices. Issue 14 (20th March 2019) - Cheng, Rui; Li, Fucheng; Zhang, Jiahui; She, Xingjin; Zhang, Yi; Shao, Kejin; Lin, Yuxuan; Wang, Cai-Feng; Chen, Su
Abstract : An easy-to-perform interfacial synthesis method is demonstrated to achieve amphiphilic quantum dots with a high photoluminescence quantum yield, which are useful for high-color-quality light-emitting applications. Abstract : To realize the potential of quantum dots (QDs) in various applications, good affinity between QDs and diverse media with different polarities is particularly important. Herein, we develop an interfacial synthesis method to achieve brightly fluorescent amphiphilic CdSe/ZnS QDs modified with beta-cyclodextrin (β-CD) to realize diversified functional applications. Thanks to the host–guest assembly between β-CD and the surface ligand of QDs under the moderate interfacial conditions, the beforehand prepared lipophilic QDs change into amphiphilic ones; the as-synthesized amphipathic QDs have good dispersibility in water and toluene, along with greatly enhanced photoluminescence (PL) quantum yields (QYs) of 80–82%. We then demonstrate the use of amphiphilic QDs as colour conversion materials to construct a liquid crystal display (LCD) backlight with a wide colour gamut up to 112%. The amphiphilic QDs could also be well incorporated into polymers via microfluidic spinning to fabricate brightly fluorescent fabrics useful for flexible optoelectronic devices. This work presents a facile functional platform that enables the realization of amphiphilic QDs for high-colour-quality light-emitting applications.